Animation, Incidental Learning, and Continuing Motivation - Rieber, Lloyd P (Journal of educational psychology, 1991)
Effects of animated graphics presentations on incidental learning and the degree to which various computer practice activities contain intrinsically motivating characteristics were studied with 70 fourth graders learning about Newton's laws of motion. Incidental learning occurred without sacrifice of intentional learning. Students were highly motivated to practice the computer activity. (SLD)